Exposure to polycyclic aromatic hydrocarbons in petrochemical industries by measurement of urinary 1-hydroxypyrene. - Boogaard, P J (1994)
Biological monitoring of exposure of workers to polycyclic aromatic hydrocarbons (PAHs) in petrochemical industries was performed by the measurement of urinary excretion of 1-hydroxypyrene. In 121 of the 462 workers studied (both smokers and non-smokers) who had had no recent occupational exposure to PAHs a median 1-hydroxypyrene concentration of 0.21 micrograms/g creatinine was found. The upper limit of the 95% confidence interval in these workers of 0.99 micrograms/g creatinine was used as the upper normal value for industrial workers. Urinary 1-hydroxypyrene concentrations were measured in workers involved in manufacture and maintenance operations in oil refineries (13 studies in eight different settings), in workers manufacturing or handling products containing PAHs in chemical plants (five studies in three settings) and laboratories (four studies), and in workers digging soil contaminated with PAHs (three studies). In most studies in oil refineries 1-hydroxypyrene concentrations were only marginally greater than the values measured in the 121 workers with no recent occupational exposure to PAHs. This was also the case in maintenance operations with higher potential exposure to PAHs, indicating that personal protection equipment was generally adequate to prevent excessive exposure. The studies in chemical plants also showed that exposure to PAHs is low. An exception was the workers engaged in the production of needle coke from ethylene cracker residue, where increased urinary 1-hydroxypyrene concentrations were measured. The excretion of 1-hydroxypyrene by the operators and maintenance workers of this plant was investigated in relation to potential methods of exposure to PAHs. Dermal and inhalatory exposure were both significant determinants of exposure to PAHs.